Phylogenomic Analyses Reveal Species Relationships and Phylogenetic Incongruence with New Member Detected in Allium Subgenus Cyathophora - Kun Chen; Zi-Jun Tang; Yuan Wang; Jin-Bo Tan; Song-Dong Zhou; Xing-Jin He; Deng-Feng Xie (Plants)
Species characterized by undetermined clade affiliations, limited research coverage, and deficient systematic investigation serve as enigmatic entities in plant and animal taxonomy, yet hold critical significance for exploring phylogenetic relationships and evolutionary trajectories. Subgenus Cyathophora (Allium, Amayllidaceae), a small taxon comprising approximately five species distributed in the Qinghai–Tibet Plateau (QTP) and adjacent regions might contain an enigmatic species that has long remained unexplored. In this study, we collected data on species from subgenus Cyathophora and its close relatives in subgenus Rhizirideum, as well as the enigmatic species Allium siphonanthum. Combining phylogenomic datasets and morphological evidence, we investigated species relationships and the underlying mechanism of phylogenetic discordance. A total of 1662 single-copy genes (SCGs) and 150 plastid loci were filtered and used for phylogenetic analyses based on concatenated and coalescent-based methods. Furthermore, to systematically evaluate phylogenetic discordance and decipher its underlying drivers, we implemented integrative analyses using multiple approaches, such as coalescent simulation, Quartet Sampling (QS), and MSCquartets. Our phylogenetic analyses robustly resolve A. siphonanthum as a member of subg. Cyathophora, forming a sister clade with A. spicatum. This relationship was further corroborated by their shared morphological characteristics. Despite the robust phylogenies inferred, extensive phylogenetic conflicts were detected not only among gene trees but also between SCGs and plastid-derived species trees. These significant phylogenetic incongruences in subg. Cyathophora predominantly stem from incomplete lineage sorting (ILS) and reticulate evolutionary processes, with historical hybridization events likely correlated with the past orogenic dynamics and paleoclimatic oscillations in the QTP and adjacent regions. Our findings not only provide new insights into the phylogeny of subg. Cyathophora but also significantly enhance our understanding of the evolution of species in this subgenus.